Understanding the Predictive Potential of the Oral Microbiome in the Development and Progression of Early Childhood Caries - Duque, Cristiane [UNESP]; Chrisostomo, Daniela Alvim [UNESP]; Souza, Amanda Caselato Andolfatto [UNESP]; Braga, Gabriela Pacheco de Almeida [UNESP]; Dos Santos, Vanessa Rodrigues [UNESP]; Caiaffa, Karina Sampaio [UNESP]; Pereira, Jesse Augusto [UNESP]; de Oliveira, Warlley Campos [UNESP]; Ribeiro, Apoena de Aguiar; Parisotto, Thaís Manzano (Bentham Science Publishers, 2023)
Background: Early childhood caries (ECC) is the most common chronic disease in young children and a public health problem worldwide. It is characterized by the presence of atypical and fast progressive caries lesions. The aggressive form of ECC, severe early childhood caries (S-ECC), can lead to the destruction of the whole crown of most of the deciduous teeth and cause pain and sepsis, affecting the child's quality of life. Although the multifactorial etiology of ECC is known, including social, environmental, behavioral, and genetic determinants, there is a consensus that this disease is driven by an imbalance between the oral microbiome and host, or dysbiosis, mediated by high sugar consumption and poor oral hygiene. Knowledge of the microbiome in healthy and caries status is crucial for risk monitoring, prevention, and development of therapies to revert dysbiosis and restore oral health. Molecular biology tools, including next-generation sequencing methods and proteomic approaches, have led to the discovery of new species and microbial bi-omarkers that could reveal potential risk profiles for the development of ECC and new targets for anti-caries therapies. This narrative review summarized some general aspects of ECC, such as defi-nition, epidemiology, and etiology, the influence of oral microbiota in the development and progression of ECC based on the current evidence from genomics, transcriptomic, proteomic, and metabolomic studies and the effect of antimicrobial intervention on oral microbiota associated with ECC. Conclusion: The evaluation of genetic and proteomic markers represents a promising approach to predict the risk of ECC before its clinical manifestation and plan efficient therapeutic interventions for ECC in its initial stages, avoiding irreversible dental cavitation.
Keywords: antimicrobial agents; Early childhood caries; genome; metabolome; oral microbiome; transcriptome